Physical Characteristics of Briquettes Made of Oil Palm Empty Fruit Bunches (EFB) Using Brown Algae Adhesive - Dewita, Ana; Faisal, M.; Gani, Asri (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2020)
The charcoal produced from oil palm empty fruit bunches pyrolysis can be utilised as environmentally friendly alternative fuel briquettes. This research studied the physical characteristics of EFB briquettes using brown algae as an adhesive. The effect of the concentration of brown algae adhesive on briquette quality was investigated. The briquettes were prepared from EFB charcoal by adding adhesive at various concentrations of 2.5%, 5%, 7.5% and 10% (w/w). Subsequently, proximate analysis was performed on EFB and brown algae. The best-quality briquettes were obtained by adding brown algae adhesive at 2.5% concentrate, which resulted in a calorific value of 21,405 J/g. Other characteristics, such as moisture content, ash content, volatile matter and fixed carbon, were found to be 7.4%, 4.9%, 79% and 8.7%, respectively. Thermal characteristics, such as density, flash point and burning time, were found at 0.96 g/cm3, 5.1 seconds and 300 minutes, respectively.